Dystrophin gene analysis in Duchenne/Becker dystrophy in a Malaysian population using multiplex polymerase chain reaction - Tan, J.; Chan, J.H.M.; Tan, K.L.; Annuar, A.A.; Lee, M.K.; Goh, K.J.; Wong, Kum Thong (2010)
Dystrophinopathy is the commonest form of muscular dystrophy and comprises clinically recognized forms, Duchenne dystrophy and Becker dystrophy. Mutations in the dystrophin gene which consist of large gene deletions (65), duplications (5) and point mutations (30) are responsible for reducing the amount of functional dystrophin protein in skeletal muscle fibres leading to fibre destruction and disease. The aims of this study are to investigate the detection rate, types and distribution of large gene deletions in Malaysian dystrophinopathy patients using the multiplex polymerase chain reaction (MPCR). MPCR of 18 "hot-spot deletion" regions along the dystrophin gene was performed on DNA from 48 muscle biopsy-confirmed cases of dystrophinopathy. A positive detection rate of 58 (28/48) was observed, where 84 (16/19) Indian, 35 (6/17) Chinese and 50 (6/12) Malay ethnic groups showed deletions in their dystrophin genes. The Malaysian Indians appear to have a higher prevalence for large gene deletions compared to the Chinese and Malays. Further analyses of 42 confirmed positive cases (present 28 plus previous 14 cases) by MPCR showed the majority of deletions were in the mid-distal region of the dystrophin gene (81 in exons 45-60). The MPCR is a specific and sensitive method for confirmation of gene deletions responsible for dystrophinopathy.